EFL Students’ Perception on The Use of Coping Strategies to Overcome Burnout in Writing - Wira Zaky, Andi Rifqy; Sunra, La; Talib, Ahmad (State University of Makassar, 2022)
This study aims to determine students' perceptions on the use of coping strategies to overcome burnout when writing for the thesis of English Education students at Universitas Negeri Makassar. This research uses a descriptive-qualitative method. The participants in this study were students in class 2020. Data collection was done through interviews. Based on the results of the interview in general, participants have positive and negative perceptions of the use of coping strategies in overcoming burnout using problem-focus coping and emotional-focus coping. The data results show that students have a more positive perception of the use of coping strategies in overcoming burnout when writing a thesis.Keywords: Perception, Coping strategy, Burnout.